The most important characteristics of Kubeisa dialect as one qiltu dialects: (A Phonological Study) - Fahad, Rawaa Saadoun; Ahmed, Muslih Shwaysh (Al-Adab Journal, 2023)
This research presents briefly Iraqi Arabic dialects including KIA which is under investigation. It sheds on the main characteristics which are the main concern in this research which distinguish the qiltu dialects from other gilt dialects. This may be due to the fact that Kubeisa is a small town located far from urban regions which remains a "virgin territory" that the dialect spoken by its people requires analysis and investigation . In addition to the investigation of segmental phonemes and sounds in context (Deflexion) in Kubeisa Iraqi Arabic (KIA), this study also aimed at pointing out whether this dialect belongs to "qiltu - dialects" or "gilt - dialects" spoken in Iraq. Then the dialect under investigation in this research, i-e., segmental phonemes of KIA are presented. The phonological analysis of the segmental phonemes of KIA was the focus of the current study’s explanatory qualitative design, which involved gathering and analyzing qualitative data. The analysis of taped content, comprising sentences and words said by KIA speakers using a tape-recording equipment, is the focus of the current work. In addition, audio recording equipment is used. This study is a qualitative inquiry that is based on the words and writing created by a small group of KIA speakers. This study is descriptive since it deals with information that was gathered in the form of Instead of statistics, use recorded speech or conversations. This research concentrates on conducting interviews with KIA speakers and leveraging the instruments for recording audio activity. In this research, the researcher uses interviews which consist of several preset topics that are addressed to people who become the research subjects. To acquire qualitative data, the current study used semi-structured interviews. A semi-structured interview is one in which questions are prepared ahead of time but the interviewer is permitted to add several questions that were not planned ahead of time during the interview Also, it presents a brief survey of the main dialects used in the west of Iraq, namely HIA and RA (Dlaim Arabic). This research presents the most important results and discussion of findings of data analysis. In conclusion, the most important points in which the research is conducted are presented.